2013
DOI: 10.1007/s10943-013-9713-2
|View full text |Cite
|
Sign up to set email alerts
|

In Search of Serenity: Religious Struggle Among Patients Hospitalized for Suspected Acute Coronary Syndrome

Abstract: Hospitalization for a sudden cardiac event is a frightening experience, one that is often marked by uncertainty about health status, fear of recurrent cardiac problems, and related existential, religious, and spiritual concerns. Religious struggle, reflecting tension and strain regarding religious and spiritual issues, may arise in response to symptoms of acute coronary syndrome (ACS). The present study examined the prevalence and types of religious struggle using the Brief RCOPE, as well as associations betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
14
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 42 publications
2
14
0
Order By: Relevance
“…Investigations point to a normative character of R/S struggles that constitute an important and expected part of human life (Exline et al 2014a(Exline et al , 2014bExline and Rose 2005;Magyar-Russell et al 2014;Sedlar et al 2018;Tobin and Slatcher 2016). In fact, some theologians maintain that religious doubts are inevitable and may play a beneficial role in personal spiritual growth (Ellison et al 2013).…”
Section: Religious and Spiritual Strugglesmentioning
confidence: 99%
See 1 more Smart Citation
“…Investigations point to a normative character of R/S struggles that constitute an important and expected part of human life (Exline et al 2014a(Exline et al , 2014bExline and Rose 2005;Magyar-Russell et al 2014;Sedlar et al 2018;Tobin and Slatcher 2016). In fact, some theologians maintain that religious doubts are inevitable and may play a beneficial role in personal spiritual growth (Ellison et al 2013).…”
Section: Religious and Spiritual Strugglesmentioning
confidence: 99%
“…A significant body of literature (Sedlar et al 2018) has revealed that religious/spiritual (R/S) struggles are not uncommon and are strongly interconnected with greater health problems (McConnell et al 2006). People can struggle with their faith in response to trauma or stressful events (Currier et al 2018), a serious, life-threatening experience such as heart failure (Magyar-Russell et al 2014;Park et al 2011), different forms of cancer (Fitchett et al 2004;Sherman et al 2005), bereavement (Burke and Neimeyer 2014;Cowchock et al 2010;Neimeyer and Burke 2011), indicators of emotional distress (Exline and Rose 2005) such as anxiety (Zarzycka and Zietek 2018) and depression (Exline et al 2000;Murphy et al 2016), and a lower well-being or satisfaction with life (Wilt et al 2016;Zarzycka and Zietek 2018). R/S struggles might be related to extrinsic, intrinsic, and quest religiousness (Hill and Pargament 2008), as well.…”
Section: Introductionmentioning
confidence: 99%
“…Conceptualizations of religion developed by health psychology researchers may have implications for links between RS and health. These conceptualizations include concepts of meaning making (Park, 2012), reappraisal (Dezutter et al, 2011), sense of community (LaPierre, 1994), sense of reverence (Ai et al, 2011), and relief of existential distress (Magyar-Russell et al, 2014). …”
Section: Future Directions Anticipated Barriers and Research Recommmentioning
confidence: 99%
“…Negative religious coping is a general term used to describe maladaptive ways religion can be used to cope. Religious struggle, is a specific type of negative religious coping that is marked by tension and strain about religious and spiritual issues, the reinterpretation of stressors as punishment from the sacred, and/or spiritual discontent (Magyar-Russell et al., 2014). Religious struggle is a normative and expected process in dealing with life stress with outcomes dependent on how these struggles are managed, such that resolved religious struggles are associated with growth and transformation but unresolved religious struggle or strain is linked with hopelessness and poor psychological health (Magyar-Russell, et al, 2014; Pargament, Murray-Swank, Magyar, & Ano, 2005).…”
mentioning
confidence: 99%
“…Religious struggle, is a specific type of negative religious coping that is marked by tension and strain about religious and spiritual issues, the reinterpretation of stressors as punishment from the sacred, and/or spiritual discontent (Magyar-Russell et al., 2014). Religious struggle is a normative and expected process in dealing with life stress with outcomes dependent on how these struggles are managed, such that resolved religious struggles are associated with growth and transformation but unresolved religious struggle or strain is linked with hopelessness and poor psychological health (Magyar-Russell, et al, 2014; Pargament, Murray-Swank, Magyar, & Ano, 2005). Positive religious coping has been linked with lower levels of anxiety and better physical well-being, whereas religious struggle is associated with greater depressive symptoms, poor physical health, and even greater risk of mortality (Ai, Seymour, Tice, Kronfol, & Bolling, 2009; Sherman, Simonton, Latif, Spohn, & Tricot, 2005).…”
mentioning
confidence: 99%